Efek Potensial Pengembangan Sparkol Videoscribe terhadap Hasil Belajar Mahasiswa - Rani Refianti; Idul Adha (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
ABSTRACT This study aims to determine the potential effect of developing sparkol videoscribe-based learning media on student learning outcomes of STKIP PGRI Lubuklinggau. This research is a development research using a 4D development model. This model consists of 4 stages of development, namely define, design, develop and disseminate. An assessment of student learning outcomes was conducted to determine the potential effect of developing sparkol videoscribe. Assessment of student learning outcomes is carried out by giving test questions after the learning is completed. The results of the research, the development of sparkol videoscribe has a positive potential effect, where 50% of students are in the very satisfactory category, 33.33% of students are in the satisfactory category and 16.66% of students are in the moderate category. In conclusion, the development of the sparkol videoscribe learning media that has been carried out has a potential effect on student learning outcomes. Keywords: Potential Effects, Learning Outcomes, Development, Sparkol